The implementation of school-based lesson study at elementary school - Purnomo Purnomo (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2017)
This study aims to describe and interpret the implementation of school-based lesson study in SDN I Kretek. This study uses the qualitative research. The data were collected through in-depth interviews, participant observation, field notes, and documentation. The data validity was determined through sources and techniques triangulation. The data were analyzed using the Interactive Analysis Model from Miles and Huberman. The results show: (1) the planning of school-based lesson study program at SDN 1 Kretek has been implemented from the beginning of the school year 2014/2015 by establishing school-based lesson study team. This team is responsible for planning, managing, and evaluating school-based lesson study program at SDN 1 Kretek, (2) school-based lesson study at SDN 1 Kretek is implemented in three phases, namely planning, implementation, and reflection, and (3) The evaluation of lesson study is conducted by each teacher who has conducted the open class and conducted thoroughly with a meeting by a team of school-based lesson study SDN 1 Kretek at the end of the school year.